THE EFFECTIVENESS OF ENTREPRENEURIAL SPIRIT VALUES AGAINST SUCCESS AT UD. SIMPANG JODOH TEMBUNG PERCUT SEI TUAN - Finta Aramita; Dahrul Siregar; Agus Salim Harahap; Baginda Harahap (SEAN Institute, 2022)
The purpose of this study is to evaluate the impact of entrepreneurial spirit on business success in UMKM UD. Simpang Jodoh Tembung Percut Sei Tuan, exploratory research was the method employed in this study, and a Likert scale was used to measure the variables. A questionnaire, interviews, and research documents that must be completed make up the data collection methodology. UD. Simpang Jodoh Tembung Percut Sei Tuan is the population being studied. The saturated sampling technique, also known as the census, was used to conduct 40 UMKM Sampling in total. 40 participants made up the study's relatively small population. Using SPSS version 23 software, data processing including descriptive analysis, hypothesis testing, and multiple regression analysis was done. The findings demonstrated that the factor effectiveness of the value of the entrepreneurial spirit on the success of a business has a positive and significant effect partially or simultaneously in UMKM UD. Simpang Jodoh Tembung Percut Sei Tuan.